Experimental and numerical investigations of laced built-up lightweight concrete encased columns subjected to cyclic axial load - Divyah, Nagarajan; Prakash, Ramaiah; Srividhya, Sundaresan; Avudaiappan, Siva; Guindos, Pablo; Maureira Carsalade, Nelson.; Prakash Arunachalam, Krishna.; Noroozinejad Farsangi, Ehsan.; Roco Videla, Ángel Gerardo. (MDPI, 2023)
The steel-concrete composite column comprises a steel core and surrounding concrete. The purpose of the system is to provide analysis and design techniques for a newly invented class of laced steel-concrete composite short columns for cyclic axial loads. To minimize the increasing density issues associated with nominal strength concrete and in consideration of the depletion of natural resources required to produce concrete, factory-obtained lightweight sintered fly ash aggregates with and without basalt fiber are employed. The normal-weight concrete containing basalt fiber is shown to be more ductile than any other column. The axial deformation of columns LNA and LSA at failure was found to be 3.5 mm, whereas columns LNAF and LSAF reached an axial shortening of 4.5 mm at failure. The column LSAF was found to have 5.3% more energy absorption than the LSA and 11.5% less than the column LNAF. It was observed that the rigidity of these fabricated components had been enhanced. It was found that the section configuration with a lacing system had improved confinement effects and ductility. Comparing the finite element analysis to the experimental data revealed a strong connection with numerical modeling, with a variance of around 8.77%.
Keywords: Laced built-up column; Basalt fiber; Strain behavior; Finite element; Deformation; Hormigón liviano